2014
DOI: 10.4236/lce.2014.51002
|View full text |Cite
|
Sign up to set email alerts
|

GEF Experiences in Closing the Global Energy Efficiency Gap

Abstract: The term "energy efficiency" has been widely used in global energy, economics, and environment, and it is well known that energy efficiency is one of the most cost-effective approaches in saving energy and mitigating greenhouse gas (GHG) emissions. However, it is still not clear how many metric tons of carbon dioxide (MTCO 2 ) can be mitigated if one dollar is invested in worldwide energy efficiency. This study tries to clear this issue. Using data of 49 completed energy efficiency projects funded by the Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Foreign actors such as bilateral donors and multilateral development banks can play a key role in addressing energy transition bottlenecks. They can facilitate the flow of knowledge, technological and financial resources, and organizational capabilities in energy efficiency [15], wind [16], and geothermal power projects [17]. They can also address policy, institutional, and regulatory barriers [18,19], and create industrial networks [16] on different theoretical grounds [20].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign actors such as bilateral donors and multilateral development banks can play a key role in addressing energy transition bottlenecks. They can facilitate the flow of knowledge, technological and financial resources, and organizational capabilities in energy efficiency [15], wind [16], and geothermal power projects [17]. They can also address policy, institutional, and regulatory barriers [18,19], and create industrial networks [16] on different theoretical grounds [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed both in quantitative and qualitative results (Yang et al, 2014). However, the market penetration of energy efficient technologies is generally hindered by barriers that are effected by prices, financing, international trade, structure of market institutions, information provision and socio-cultural and behavioral issues.…”
Section: Introduction-mentioning
confidence: 78%
“…Training staff and institutions on how to conduct longterm energy planning that incorporates energy efficiency can add value, so many bilateral and multilateral assistance programs have been building capacity around the world for decades [23]. The full life cycle of energy efficiency options requires at least some individual and institutional capability, as exemplified in the stakeholder discussion below.…”
Section: Institutional and Human Capacity Buildingmentioning
confidence: 99%
“…From the perspective of consumers and stakeholders, consumers may not understand the benefits of electro-technologies; some worry that building reliability might be compromised if all energy comes from one source (no gas line to serve as potential backup if the electricity goes out 23 ); some may experience range anxiety with electric vehicles. Contractors who lack familiarity with electro-technologies would be less likely to provide consultation, installation, and maintenance services on them.…”
Section: Benefits and Challenges Of Electrificationmentioning
confidence: 99%